(untitled) (Medico Legal Update, 2020)
Objective(s): The aim of the study is to evaluate the physically- disabled fighters’ quality of life, and to identify the relationship between the physically-disabled fighters’ quality of life and their socio-demographic characteristics. Method: A quasi-experimental design is carried throughout the present study at the Rehabilitation Military Center in Al-Basra City, Iraq,for the period of January 7th 2019 to October 31st 2019. Non-probability “purposive” sample of (27) physically disabled fighters’ is selected selected for the present study. The questionnaire is composed of two main parts (The Physically Disabled Socio-Demographic Characteristics, and Physically Disabled Fighters’ Quality of Life Evaluation Tool).The data are collected through the utilization of a developed questionnaire (Arabic version) and the use of structured interview technique with each physically disabled fighter as means of data collection. Test-retest reliability of instrument was determined through the use of Pearson correlation coefficient and content validity of the instrument validity was determined through a panel of (18) experts. Data were analyzed through the use of descriptive statistical data analysis approach of frequency, percentage, mean, mean of scores, total of scores, range and standard deviation and inferential statistical data analysis approach T-test, multiple linear regressions, person correlation coefficient,Chi-Square test, and analysis of variance (ANOVA). Results: The results of the study depict that the evaluation of physically-disabled fighters’ quality of lifeis moderate on the physical health domain,psychological health domain, and social relationship domain environment domain and spiritual health domain, and low on the level of independence domain; physically disabled fighters’ quality of life is significantly different relative to their age, residency, level of education, and chronic illness. Conclusion: The study concluded that the overall evaluation of physically-disabled fighters’ quality of life is moderate.